2022
DOI: 10.3389/fpubh.2022.981484
|View full text |Cite
|
Sign up to set email alerts
|

Potential mediators of the link between wealth index and anthropometric indices of under-five children in Ethiopia

Abstract: BackgroundMalnutrition of under-five children has adverse effects on child's health and development, such as growth failure and muscle wasting. The household wealth index has a direct contribution to child malnutrition despite little attention being given to its indirect effect through other factors. This study aimed to identify the potential mediators of the link between wealth index and malnutrition.MethodsIn this study, a cross-sectional study design was implemented based on the data obtained from the 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
3
1
0
Order By: Relevance
“…According to the current study, children from lower-class families are more likely than their counterparts to be impacted by the CIAF. This is consistent with earlier research done in many nations [ 42 , 43 , 52 ]. This could be the case because the wealthiest households can afford to buy different types and amounts of food for their kids, while poorer homes may have less access to health care services than wealthier ones.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…According to the current study, children from lower-class families are more likely than their counterparts to be impacted by the CIAF. This is consistent with earlier research done in many nations [ 42 , 43 , 52 ]. This could be the case because the wealthiest households can afford to buy different types and amounts of food for their kids, while poorer homes may have less access to health care services than wealthier ones.…”
Section: Discussionsupporting
confidence: 94%
“…The findings showed that female children had a lower risk of having CIAF than male children from a similar socioeconomic background. This study is consistent with previous studies [ 38 , 43 ], It could possibly be a factor in CIAF because of the biological growth and vulnerability of men and the fact that the percentage of male preterm births is higher than that of female preterm births [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…The effect of household wealth was fully mediated, and the hypothesis in the conceptual structural model is supported. This finding is supported by other studies [ 11 , 12 , 22 , 32 , 33 , 54 , 65 , 66 , 67 ].…”
Section: Discussionsupporting
confidence: 90%
“…This result is consistent with that of Ahinkorah et al, [4] that reported TBM to be less likely to occur among female compared to male children. Several studies have shown that being a female child is strongly tied to lower odds of undernourishment in Ethiopia [36][37][38][39][40][41].…”
Section: Plos Global Public Healthmentioning
confidence: 99%